686 Sleep Education and Sleep Outcomes in the Time of Covid-19 in Mexico. (3rd May 2021) - Baldwin, Carol; Gamiño, Sergio Marquez; de la Cruz, Carolina Cabrera; Quan, Stuart
Abstract: Introduction: This study examines computer-mediated sleep education for health providers enrolled in a certified diabetes educator program in November 2020 in Mexico. Methods: Data derived from pre/post ratings assessed knowledge of obstructive sleep apnea (OSA), insomnia, restless legs syndrome (RLS), short sleep duration (SSD), circadian rhythm disorders (CRD), and drowsy driving (DD) on a 5-point Likert-like scale, and five true/false questions regarding misconceptions about sleep. Outcomes included self-reported sleep problems among providers since the onset of the March 2020 Covid-19 surge in Mexico. Pre/post means were compared with paired t-tests using SPSS (V25) with significance set at p<0.05. Results: Volunteer participants (N=23; 83% women; 52% nutritionists; 48% health providers) were recruited from the fall semester 2020 diabetes educator certificate program. Means with standard deviations showed significant learning for all sleep disorders following the training (OSA: 3.1±1.0 to 4.4±0.78; Insomnia: 3.2±0.85 to 4.3±0.82; RLS: 2.1±1.2 to 4.2±0.95; SSD: 2.7 ±1.1 to 4.4±0.72; CRD: 2.6±1.2 to 4.4±0.73; DD: 2.6±1.1 to 4.4±0.78, all p<.0001). The total pre- to post-scores (Range=0 to 30) for sleep disorders moved from 16.3±5.7 to 26.3±4.4, p<.0001. Participants demonstrated improved, but borderline significant findings regarding misconceptions about sleep from pre-to post-testing, p=.07. Of the 23 respondents, 18 (78%) reported sleep problems specific to the onset of the Covid-19 pandemic in Mexico. Of the 18 providers, 13 reported insomnia symptoms, while five indicated short sleep due to double shift work, anxiety and depression, or poor sleep quality. Conclusion: Participants (78%) reported sleep problems; particularly insomnia associated with anxiety, depression, poor sleep quality and extended shift work since the onset of the Covid-19 pandemic. Findings are consistent with global studies of Covid-19 and sleep of health care workers. Online participants' significant learning for all sleep disorders was coherent with in-class learners (N=173). Pre-to-post analyses of misconceptions about sleep, particularly sleep needs for adults and that daytime sleep can make up for lack of nighttime sleep, however, were not significant for these learners compared to the in-class learning groups. Support (if any): N/A